DIGITALIZATION OF REGIONAL FINANCIAL REPORTS PUBLICATION - Irma Irma (BADAN PENERBIT STIEPARI PRESS, 2023)
Disclosure of digitization is considered capable of reaching all aspects of society and can be accessed at any time. Advances in technology will make all information accessible easily, cheaply, and quickly. This study aims to analyze the effect of government size, accessibility, and audit opinion, on the digital disclosure of local government financial reports. The population and research sample are the Regional Government Financial Statements. West Java Province as many as 27 Regency and City Governments for the 2020-2022 Fiscal Year have been audited by the Supreme Audit Agency. The analysis technique uses multiple regression with the Fixed Effect Model. The results show all independent variables namely government size, accessibility